Benefits of eggshell reinforcement in water sorption and color stability of heat-cured polymethyl-methacrylate provisional fixed partial dentures - Ricca Chairunnisa; Syafrinani; Wijaya, Olivian (Indonesian Journal of Prosthodontic, 2024)
Background: Oral rehabilitation procedures such as crown lengthening, implants for anterior teeth, and endodontic procedures with limited tooth structure require provisional restoration for a long time. The material used in fabricating provisional fixed partial dentures is polymethyl-methacrylate (PMMA). PMMA is divided into heat cured and self-cured based on the polymerization. Heat-cured PMMA has better mechanical properties than self-cured PMMA. Despite its advantages, however, there are also some disadvantages, such as high water sorption, low color stability, and wear of use. Research on the use of eggshells as reinforcement in denture bases has been conducted. However, the use of eggshells in provisional fixed partial dentures has not been done yet. Eggshell, as an environment by-product waste material, is composed of 95% calcium carbonate (CaCO3), magnesium, potassium, and other inorganic components, can be used as alternative natural reinforced materials for PMMA provisional restoration.Objectives: To describe use of provisional restoration for a long time, PMMA as provisional restoration material, as well as the merit of eggshell as natural reinforcement material in water sorption and color stability of heat-cured PMMA provisional fixed partial dentures.Conclusion: Eggshell, which is composed of calcium carbonate, can be converted into hydroxyapatite as a reinforcement in long term provisional restoration, could improve the physical properties of heat-cured PMMA, such as water sorption and color stability.